Antioxidant, enzymes inhibitory, physicochemical and sensory properties of instant bio-yoghurts containing multi-purpose natural additives - Irondi, Emmanuel Anyachukwu; Bankole, Abigael Odunayo; Awoyale, Wasiu; Ajani, Emmanuel Oladipo; Alamu, Emmanuel Oladeji (Frontiers in Nutrition, 2024)
This study aimed to assess the antioxidant, enzyme inhibitory, physicochemical and sensory properties of instant bio-yoghurts containing multi-purpose natural additives. Multi-purpose natural additives were formulated with three natural additives (sweet detar seed, ginger rhizome, and hibiscus calyx flours, as as a thickener, flavourant and colourant, respectively) blends at proportions derived from the Design Expert. The additives' synthetic counterparts were formulated with sodium carboxymethylcellulose, vanilla flavour, and red colourant at the same proportions. After that, yoghurt was produced and the additives blends were incorporated into it either in aqueous extract or flour form, yielding bio-yoghurts designated multi-purpose natural additive extract-containing yoghurt (MNAE-yoghurt), multi-purpose natural additive flour-added yoghurt (MNAF-yoghurt), and their multi-purpose synthetic additives-containing counterparts (MSAE-yoghurt and MSAF-yoghurt). A commercially-available bio-yoghurt served as a control.All the yoghurts were lyophilized to obtain instant bio-yoghurts. Subsequently, bioactive components (total phenolics, tannins, total flavonoids and saponins), antioxidants and enzymes [alpha-amylase, alpha-glucosidase, pancreatic lipase, and angiotensin 1-converting enzyme (ACE)] inhibitory activities, as well as proximate, physicochemical and sensory qualities of the bio-yoghurts were determined. The MNAE-yoghurt and MNAF-yoghurt had higher bioactive constituents, total titratable acid levels, and more potent antioxidant and enzyme inhibitory properties, but a lower pH than their synthetic counterparts and the control. The total phenolics, tannins, total flavonoids and saponins levels of MNAE-yoghurt and MNAF-yoghurt were 14.40±0.24 and 16.54±0.62 mg/g, 1.65±0.04 and 1.74±0.08 mg/g, 4.25±0.03 and 4.40±0.02 mg/g, 0.64±0.01 and 0.66±0.02 mg/g, respectively. Among the natural multi-purpose additivescontaining bio-yoghurts, MNAF-yoghurt had higher bioactive constituents and stronger antioxidant and enzymes inhibitory properties. Its α-amylase, α-glucosidase, ACE, and pancreatic lipase IC50 values were 72.47±0.47, 74.07±0.02, 25.58±2.58, and 33.56±29.66 µg/mL, respectively. In contrast, MNAE-yoghurt had the highest protein (13.70±0.85%) and the lowest fat (2.63±0.71%) contents. The sensory attributes of all the bio-yoghurts fell within an acceptable likeness range. Overall, the inclusion of multi-purpose natural additives blends enhanced the instant bio-yoghurts' nutritional, health-promoting, and sensory qualities.